Pregnenolone, Dehydroepiandrosterone, and Schizophrenia: Alterations and Clinical Trials - Ritsner, Michael S. (CNS Neurosci Ther, 2010)
Neurosteroids, such as pregnenolone (PREG), dehydroepiandrosterone (DHEA), and their sulfates (PREGS and DHEAS) are reported to have a modulatory effect on neuronal excitability and synaptic plasticity. They also have many other functions associated with neuroprotection, response to stress, mood regulation, and cognitive performance. Furthermore, these neurosteroids have been linked to, and their levels are altered in, neuropsychiatric disorders. This review highlights what is currently known about the metabolism and mode of action of PREG and DHEA, as well as about alterations of these neurosteroids in schizophrenia. This review also provides substantial information about clinical trials with DHEA and PREG augmentation with of antipsychotic agents in schizophrenia.